Effect of Various Concentration of Vegetable Protein in Hair Mask on The Hair Texture - Ivony Helen; Idajani Hadinoto; Lannie Hadisoewignyo; Lisa Soegianto (Indonesian Journal of Cancer Chemoprevention, 2011)
Effect of various concentrations of vegetable protein in hair mask on the hair texture including hair smoothness, hair shining, hair strength, and morphology of hair had been studied. Concentrations of vegetable protein are made 5%, 7.5%, and 10%. The hair mask was evaluated such as organoleptic, pH, viscosity, and allergy test. Hair mask used in six subjects that have damage hair for 8 times every 2 days. Then, the hair mask was evaluated such as hair smooth and hair shine that used tree trained panel and analyzed using non parametric method Q Cochran. Hair strength was evaluated using autograph then the results were  analyzes using ANOVA test (p<0.05), while hair morphology was evaluated using scanning microscope electron (SEM). The experimental results showed that vegetable protein in hair mask increased hair smoothness, hair strength, and morphology of damaged hair but did not give effect for hair shining. Various concentrations of vegetable protein (5%, 7.5%, and 10%) on hair mask given the same effect in hair texture (hair smoothness, hair strength, and hair morphology).Keywords: vegetable protein, hair mask, hair texture